PRINCIPALS’ MANAGEMENT TECHNIQUES FOR IMPROVING STUDENTS’ PERSONNEL SERVICES IN SECONDARY SCHOOLS IN ENUGU STATE - Ibe, Chima, Emmanuel (Journal of Continuing and Development Education, 2024)
This study was carried out to find out principals’ management techniques for improving students’ personnel services in secondary schools in Enugu state. Three research questions and three null hypotheses tested at .05 level of significance guided the study. Descriptive survey design was adopted. The population of the study are all the 298 Principals and 29 urban and ruler public secondary schools in Enugu state. Instrument for data collection was a 26 item structured questionnaire validated by three experts. The reliability of the instrument was determined using Cronbach Alpha formula and a reliability of .70 was got. Data collected was analyzed using grand mean and standard deviation to answer the three research questions while t-test statistics was used to test the three null hypotheses at 0.05 level of significance. It was revealed that management techniques used by principals to improve students’ personnel services include; admission of students are guided by available facilities, approaching philanthropic individuals to help sponsor students’ personnel services among others. It was recommended that government should train and retrain secondary school principals on current skills needed for effective management of students’ personnel services